The relationship between ownership concentration and firm performance: Empirical evidence from Thai IPOs - Sa-nguannam, Praphaporn (2010)
This research provides an empirical analysis on the relationship between ownership concentration and firm performances in both short-term and long-term of 111 Thai initial public offerings (IPOs) during January 2003 to July 2010. The short-term and long-term performances are represented as initial returns (underpricing) and aftermarket returns, respectively. The ownership concentration is measured by the concentration ratio, the stock ownership of a single largest shareholder who holds at least 50 percent of share outstanding. This paper further examines the indirect effect of ownership control through the controlling shareholders, who own at least 25 percent of a company’s shares, to gain more insight to its effect of long-term aftermarket performance. This study argues that the IPO process is not a basic step by which a firm looks for new capital, but it also involves conflicts of interest between the different shareholders, especially between the large shareholders, controlling shareholders and small or outside shareholders. The structure of corporate control plays a crucial role in the determination of the IPOs underpricing, and aftermarket return since the initial owners of a firm desire to retain control over the corporation as it result in private benefits. The key finding of this paper is that the ownership concentration of Thai IPO firms is positively associated to firm performance in both short-term and long-term. This implies firms with high ownership concentration perform better than dispersed ownership firms. Furthermore, with the ownership control through controlling shareholder, firms with higher level of controlling shareholders give better performance than firms with lower and no controlling shareholder. Whilst, firms with low level of control yield better performances than those without controlling shareholder.